Educational Choices and Outcomes of Young People Who Stammer in the UK. (30th June 2015) - Jenkins, H.; Brumfitt, S.; Stackhouse, J.
Abstract: It has been widely reported in the literature that the act of stammering can have an adverse effect on a person's educational performance, with a number of researchers suggesting that children who stammer under achieve at school. However there is limited empirical data indicating whether there is a difference in educational achievement between young people who stammer and their peers in the current UK education system. Aims: To examine the educational choices and performance of young people who stammer who are either still in education or have recently completed their education. To compare the educational attainment of young people who stammer with national attainment levels in England. To investigate if having a stammer influences decisions about subject choices. Thirty young people aged 15- 25 years old who self-reported stammering were recruited via schools, the British Stammering Association, and the National Health Service. Participants completed a questionnaire, comprising closed and open ended questions, which concerned demographic information, speech details, their subject choices, qualifications studied and factors influencing their educational choices. Their educational attainment was compared with statistics reporting pupils' educational achievement in England from the Department for Education. Participants' attainment of 5+ GCSE grades A*- C and 5+ GCSE grades A*-C, including English and Maths was found to be comparable with the results for pupils in England. Similarly, the over all percentage of participants achieving at least 2 A levels grades A*-E (or equivalent) was equal to the average for pupils in England. Out of 24 participants aged 18 years and over, almost one-third achieved an undergraduate degree (level 4 qualification) which is above the average for young people in England and Wales. A vast range of subjects were studied or were currently being studied at A level or equivalent. The most popular subject choice for A level was English (24%) followed by Information Technology (20%). Almost one-quarter of participants reported disliking subjects, involving an oral content. The majority of participants stated that their selection of subjects was guided by what they found enjoyable and interesting, but two-thirds of participants' reported their choice was influenced by their speech difficulty. One half of the participants described receiving some support with their academic choices with just one-third of these participants receiving guidance from teachers or careers advisers. The findings of this study suggest that the educational achievement of young people who stammer is comparable to pupils in England but this study is not able to draw firm conclusions from the data due to the small sample size. The majority of participants acknowledged that stammering influenced their choice of subjects studied. A second phase to this study, involving interviews with selected participants from phase one, is focusing on a more detailed exploration of the relationship between stammering and their educational experiences.